Avances en el pre-mejoramiento del arroz: Estrategias de piramidación para mejorar la tolerancia a pyricularia (pyricularia oryzae cav.) Mediante la integración de cinco genes clave - Pineda, Marcela; Agrono, Tomas; Quintero, Constanza; Morales, Mabel; Alvarez, Maria Fernanda (2024)
The fungus Pyricularia oryzae Cav., is the cause of the most important disease in rice cultivation, blast, due to its widespread presence in the world. Consequently, the development of rice plants tolerant to this disease is a key factor to maintain crop yields. By incorporating techniques such as marker-assisted selection (MAS) to screen genes of interest and the production of Double Haploid plants to generate homogeneous populations, we accelerate the development of resistant materials with several blast resistance genes. This study aims to obtain plants carrying five resistance genes to Pyricularia using molecular markers and tissue culture. Three parents were involved which have been identified as carriers of Pyricularia tolerance genes: CIFED 11 A (Pish, Pi2, and Piks-Zh), IRBLt-K59_LTH (Pi-t) and FL13032 (Pish and Pii). Two simple crosses were carried out (CIFED 11 A x IRBLt-K59 and CIFED 11 A x IRBLT-K59) and the F1 plants carrying the genes of each parent involved were selected, subsequently, A double cross was made between the two F1 to obtain a population of 1424 seeds that were planted to confirm the presence of the genes and with the selected plants the anther culture was carried out. In the tissue culture process, calluses were obtained, and plants were regenerated as a result of these. According to the phenotypic evaluation, double haploid plants were identified and evaluated to confirm the presence of the five resistance genes. Seven plants were confirmed as carriers of the genes of interest that present genotypic and phenotypic stability, which can be included in breeding program schemes for the generation of varieties tolerant to Pyricularia.